CIMBEBASIA: JOURNAL OF THE NATIONAL MESEUM OF NAMIBIA (Windhoek National Museum of Namibia, 2003)
It covers aspects of culturally-mediated knowledge and use of natural resources among contemporary Dramara farmers in southern Kunene Region.
Keywords: Culture